2011
DOI: 10.1016/j.physbeh.2010.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of male Sprague–Dawley rats to sucrose-induced obesity: Effects of 18-methoxycoronaridine

Abstract: Evidence suggests that the development of obesity in males and females might be mediated by distinct mechanisms, warranting different treatment approaches. In previous studies from this laboratory, a high sucrose diet induced excessive weight gain in female Sprague-Dawley rats and administration of a selective antagonist of α3β4 nicotinic receptors, 18-methoxycoronaridine (18-MC), prevented this form of obesity. In the present study similar parameters were studied in male rats by using an identical experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…While 18-MC has been shown to reduce self-administration of multiple drugs of abuse via the habenulo–interpeduncular pathway (e.g., Glick et al 2008), 18-MC, like other nicotinic receptor antagonists, may modulate the effects of ghrelin via a distinct mechanism. Considered together with our previous data showing attenuated sucrose reward following 18-MC treatment (Taraschenko et al 2010a, b) and recent studies implicating ghrelin in both food and drug reward (Jerlhag et al 2010), these findings indicate that α3β4 nicotinic receptors and ghrelin could be jointly involved in the regulation of food reward and drug addiction.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…While 18-MC has been shown to reduce self-administration of multiple drugs of abuse via the habenulo–interpeduncular pathway (e.g., Glick et al 2008), 18-MC, like other nicotinic receptor antagonists, may modulate the effects of ghrelin via a distinct mechanism. Considered together with our previous data showing attenuated sucrose reward following 18-MC treatment (Taraschenko et al 2010a, b) and recent studies implicating ghrelin in both food and drug reward (Jerlhag et al 2010), these findings indicate that α3β4 nicotinic receptors and ghrelin could be jointly involved in the regulation of food reward and drug addiction.…”
Section: Discussionsupporting
confidence: 73%
“…Many factors have been shown to influence ingestive behavior and taste in female rats, particularly the sex hormone estradiol (Clarke and Ossenkopp 1998; Atchley et al 2005). However, females consume sucrose more readily than males (Taraschenko et al 2010b); therefore, in order to assess sucrose drinking behavior we used female rats. In this study, day of estrous was not controlled for, rather, we used random cycling female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in studies where rats are offered sweet solutions (sucrose water or sweet milk), females show a greater hyperphagic response ( 10 , 28 , 29 ), while males only present with a persistent overconsumption and fat gain on a HFHS (high-fat high-sugar) paradigm ( 27 , 30 ). Moreover, Taraschenko et al demonstrated how the choice of palatable diet produces a contrasting sex divergent response; while a HFD (40%) induced weight gain in males only, the opposite was true for a high sucrose diet ( 11 , 31 ). Therefore, combination of fat and sugar seems to be important for the induction of hyperphagia, especially in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, sex comparisons of diet-induced obesity in the most commonly used animal model species, mice, and rats, result in conflicting findings. Female rats are reported to be more vulnerable in response to a metabolic challenge (9)(10)(11)(12). In contrast, studies in mice predominantly suggest that females are equally or less susceptible to dietary obesity, unless additionally challenged by age or ovariectomy (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, both the muscarinic (scopolamine) and nicotinic (mecamylamine) antagonists, when injected peripherally to rats, were able to disrupt the incentive motivation to obtain food reward [ 219 , 220 ], indicating that systemically administered pharmaceuticals impinging on the cholinergic system might be used to modify the rewarding value of food. Previous studies demonstrated that acute and repeated intraperitoneal injections of 18-methoxycoronaridine, an α3β4 nicotinic antagonist, resulted in a selective inhibition of sucrose solution intake in female [ 221 , 222 ] but not male [ 223 ] rats. The latter, however, in contrast to females, did not develop obesity when maintained on a high-sucrose diet, indicating that the blockade of the α3β4 nicotinic acetylcholine receptor was most efficient in the selective inhibition of appetite for sweets in subjects originally preferring this kind of food.…”
Section: Cholinergic Transmission Nicotine and Tobacco Smokingmentioning
confidence: 99%